If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3k + -1s = 7k + -21 Reorder the terms: 3k + -1s = -21 + 7k Solving 3k + -1s = -21 + 7k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-7k' to each side of the equation. 3k + -7k + -1s = -21 + 7k + -7k Combine like terms: 3k + -7k = -4k -4k + -1s = -21 + 7k + -7k Combine like terms: 7k + -7k = 0 -4k + -1s = -21 + 0 -4k + -1s = -21 Add 's' to each side of the equation. -4k + -1s + s = -21 + s Combine like terms: -1s + s = 0 -4k + 0 = -21 + s -4k = -21 + s Divide each side by '-4'. k = 5.25 + -0.25s Simplifying k = 5.25 + -0.25s
| 5(y+2)=4-7 | | =y-6y^3 | | -(x-1)-3(x+4)=x | | -(x-1)+3(x+4)=x | | 16x+12x=100 | | xy+2x-3y+2+12(x^2)y-3x(y^2)-12x+18y=16 | | 2(x-1)=-(x-3)+(4-x) | | -5.99+23.105x=-587.72x-54.936 | | 36-yi=4x+3i | | (x+2)=-(x-3) | | 5y=11x+6 | | f(x)=2x+3x-1 | | x^2-4x=x(7+x) | | -(x+2)=-(x-3) | | 12m^2-17m-5= | | 15-4x+16=11 | | -6x+15=18x-7 | | 0=-r+6 | | 0=[r+6] | | -(3x+1)=-5 | | a^2-4a+1=0 | | 4X+3-5+2X=20-3X+12 | | x(3x-2)=12x^2-2x-1 | | 9x-16=-205 | | -12x^7-4x^6= | | 7m^2+63m=0 | | -0.16-5=.66x | | -3x+8x-9=5(x-6)-3 | | -.16-5=.6x | | 3(2x-5)=7x | | f(9)=9x-4 | | 2x+17=6x+5 |